Effective properties of physically nonlinear piezoelectric composites - Telega, J.J.; Gałka, A.; Gambin, B. (Archives of Mechanics, 1998)
For piezoelectric composites with periodic microstructure and subject to stronger electric fields, an effective model has been prepared. To this end the Γ-convergence theory has been applied. Detailed convergence proof has been given. Specific cases of the internal energy have been suggested. Comments on homogenization in the case of periodically nonuniform microstructure have also been provided.